Influence of international currency relations on Kazakhstan’s economy (Journal of Economic Research & Business Administration, 2016)
The analysis of recent Kazakhstan national currency tenge exchangerate devaluation causes. Tenge devaluation is considered by the authors,first of all, as a result of influence of prevailing international currency relationson Kazakhstan economy. This situation is substantiated by analysis ofmain macroeconomic and external economic indicators, the evaluation ofinfluence of individual external and internal factors on these indicators isgiven. The first influenced fact on external markets is the slowdown of Russianeconomy and the decrease of ruble exchange rate, which significantlychanged Kazakhstan economic development, as the cheap ruble contributesto Kazakhstan enterprises’ competitiveness decrease and increase ofRussian import. The second fact is the Yuan devaluation, as China is thebiggest player on metals market, and decrease of its economy can negativelyinfluence on the level of metals prices, which are the big share ofKazakhstan export.
Keywords: national currency exchange rate; inflation targeting; devaluation; balance of payments; foreign exchange reserves; price of Brent; export customs duties.